Smart Smoke Detector - Mohamad Adenan, Mohamad Syafiq; Mas Erwan, Athirah Nabihah; Muzaffar Alfian, Mohamad Norul Hafiz (International Journal of Recent Technology and Applied Science (IJORTAS), 2021)
In the past few decades many studies and researches have taken place in order to improve security systems and to increase their level of protection in different fields. One of the major problems that security must deal with is the fire outbreak that can happen in everywhere including houses, schools, factories and many other places, and to avoid that or to minimize the damage caused by fire outbreak an IoT technology is used to control such a kind of risk. IoT is a modern system that consist of sensors and switches connected. In this project we will use temperature sensor known as (Flame sensor) with Arduino device to detect fire outbreak and to measure the amount of heat intensity generated by a fire outbreak or in a specific location in our house, offices and other places. It sometimes takes too much time for the fire station to reach to the fire outbreak location and works on extinguish the fire and so these sensors will work as an early alarm system which will send a notification to our mobile phones if any fire outbreak occurred to let us know the situation clearly and before it’s too late, we act to avoid significant damage in case the fire outbreak was observed after a long time from its outbreak.